As representações da deusa Ísis nas obras de Plutarco e Apuleio: as faces de uma divindade e seus cultos (sécs. I e II d.C.) - Santos, Ellen Juliane Bueno dos (2021)
The present dissertation aims to analyse and compare the representations of the goddess Isis and her cults. On the one hand, we analysed the representations constructed by the Greek Plutarch of Chaeronea in his work On Isis and Osiris. This treatise is an interpretation of the myth of these gods of the beginning of the II A.D century. On the other hand, we analysed the work Metamorphoses by Apuleius of Madaura. It is a novel written in Latin in the second half of the II A.D century. In this novel, a Corinthian ends up being metamorphosed into a donkey after an ill-fated practice because of his curiosity towards magic, but Isis intercedes and saved him. Based on the representations that both authors construct of Isis, an originally Egyptian goddess who suffers several changes during history, we can see how the authors adapt her to the various contexts of appropriation and domination. We believe that both authors produced religious identities of Isis that bring her closer to a function of the initiator of mysteries, i.e., a guide of the initiated to the truth contained in these rituals. Furthermore, we hold that based on this initiating function, these authors also point out how an Isiac should behave in order to meet the demands of this divinity and keep away from superstitious practices. Therefore, we aim to compare these constructed images of this divinity based on Plutarch and Apuleius.